2016
DOI: 10.1007/s11605-015-2942-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Surveillance of Hypervascular Liver Lesions in Non-Cirrhotic Patients

Abstract: A consensus surveillance protocol is lacking for non-cirrhotic patients with hypervascular liver lesions presumed to represent hepatocellular adenomas. Patients with hypervascular liver lesions <5 cm not meeting criteria for focal nodular hyperplasia or hepatocellular carcinoma underwent surveillance with contrast-enhanced magnetic resonance imaging (MRI) 6, 12, and 24 months after baseline imaging. If lesions remained stable or decreased in size, then surveillance imaging was discontinued. Between 2011 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Follow‐up every 6 months when the lesion is larger than 5 cm, and annually or biennially when the lesion has regressed to 5 cm or less, until menopause, seems justified ( Fig . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow‐up every 6 months when the lesion is larger than 5 cm, and annually or biennially when the lesion has regressed to 5 cm or less, until menopause, seems justified ( Fig . ).…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the present study is that all results were based on a large, representative cohort with long follow‐up. In 2015, Chun and colleagues undertook a retrospective cohort study of 79 patients in which they aimed to validate a surveillance algorithm for women with small HCA. They concluded that patients with an HCA smaller than 5 cm can be kept under surveillance at 6, 12 and 24 months after diagnosis, and that cessation of follow‐up may be considered if the lesion remains stable or decreases in size.…”
Section: Discussionmentioning
confidence: 99%
“…Because the study did not make the patient number explicit, it did not allow conclusions regarding the risk or even the incidence of cancer in patients with normal livers. In a recent publication, Chun et al studied 79 patients with HLL in non-cirrhotic liver that were subjected to follow-up with imaging exams 9 . Only five patients had personal histories of cancer, only 14% were subjected to some type of intervention (embolization or surgery), and none of the patients had a diagnosis of cancer during the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The major criticism for the study was the lack of a minimum follow-up time, i.e., patients were included in the study with no control imaging examinations. For patients with undetermined lesions, i.e., atypical lesions that were not biopsied or resected, a minimum follow-up period of one year or even longer is indispensable understand a lesion's behavior 9 . In the present study, this approach was followed to the extent in which only stable lesions in the 2-year period were considered as "most likely benign"; for lesions to be defined as "benign" by the proposed definition, a typical diagnosis through imaging examination, anatomopathological confirmation, size reduction or even lesion disappearance during the follow-up were necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of macroscopic haemorrhage and malignant transformation in adenomas <5 cm is 5% and 2%, respectively; the risk increases to 25% and 9%, respectively, for adenomas ≥5 cm. 6 Hepatic adenomatosis can be seen in either sex with or without oral contraceptive use 5 ; other risk factors for adenoma include glycogen storage disease and hepatic steatosis. 7 In addition, adenoma formation may be associated with germ-line HNF1A (hepatocyte nuclear factor 1α) gene mutations.…”
Section: Introductionmentioning
confidence: 99%